40 Cattle-Related Trauma: A 5 Year Retrospective Review in An Adult Major Trauma Centre. (12th October 2021) - Rhind, J H; Quinn, D; Cosbey, L; Mobley, D; Britton, I; Lim, J
Abstract: Aim: Bovine injuries are a common and significant cause of trauma, often requiring admission and operative treatment. We review all bovine related injuries over five years, both emergency and GP referrals at an adult major trauma centre in England. Method: Retrospective evaluation was undertaken using keywords through radiology referrals and hospital admissions speciality databases. Demographics were collected as well as the mechanism and the situation of injury; trauma scores were calculated using: Injury Severity Score (ISS) and Probability of Survival (Ps19). Results: Sixty-seven patients were identified retrospectively over 5 years, 44 emergency patients (including 23 major traumas) and 23 GP referrals. Combined (Emergency & GP) mean age 52 years old. 67% male. Mean ISS 11. Most common combined mechanism of injury, kicked (n = 23). In emergency patients, trampling injuries were most common. 86% of the trampled patients were major traumas. Indirect injuries mainly involved farm gates (92%). 73% of bull-related injuries were major traumas. In emergency patients' fractures were the most common primary injury (n = 20), upper limb followed by spine. In GP, soft tissue injuries were the most common. 70% of the emergency referrals required admission and 50% operations. Only one GP referral required an operation. Two patients had a Ps19 score <90. There were two mortalities. Conclusions: Cattle related injuries are a significant cause of severe morbidity and mortality. They are under-reported. Patterns of injury are similar to high velocity road traffic collisions and bull-related injuries or trampling in particular, should alert the clinician to more significant trauma.